In a nutshell: Using structural and chemical changes to establish the charring conditions of archaeological hazelnut shells. (August 2022) - Holguin, A.; Charles, M.; Mithen, S.; Schulting, R.
Abstract: Charred hazel ( Corylus sp.) nutshells are found in abundance at many archaeological sites across the northern hemisphere. This paper aims to investigate the conditions under which hazelnut shells can become charred, by comparing experimentally charred modern hazelnut shells with archaeological material shells from three western Scottish Mesolithic sites. We build on previous research by refining the temperature range investigated and use Scanning Electron Microscopy and Fourier Transform Infrared Spectroscopy in order to examine the structural and chemical changes caused by charring. We find that temperature, duration and oxygen availability are key factors, with a minimum temperature of 260 °C for a relatively long duration (c. 8 h) necessary to char shells experimentally to a degree consistent with archaeological examples. Shells still resemble archaeological specimens when charred at 500 °C for short durations (c. 0.5 h) in restricted oxygen conditions. Nutshells with higher oxygen availability became charred at slightly lower conditions, while those with low oxygen availability still resembled archaeological material at slightly higher conditions. Different scenarios regarding the events surrounding the charring process are considered and compared to other research on hazelnut shell charring. These results can guide future analytical work on hazelnut shells which require an understanding of structural and chemical changes due to charring. Such an approach would likely be informative for other nutshells or similar archaeobotanical material with a tough lignocellulosic structure. Highlights: A range of temperature, time and oxygen conditions produce modern charred hazelnut shells. Some modern charred shells resemble Mesolithic samples from western Scotland. Cellular changes caused by heating can be seen by SEM.